THE INFLUENCE OF SELF-LEARNING MODEL AND SELF-EFFICACY IN LEARNING ACHIEVEMENT - Tiara Oktaviana; Riyanto Riyanto; Wasidi Wasidi (DIADIK, 2018)
This study aims to find the influence of self direct learning model, conventional learning model, and self-efficacy of science learning achievement. This research was applied to 62 students in class IV SDN 01 Kota Bengkulu as the sample which are 32 students in group applied SDL and 30 students in group applied conventional learning model based on self-efficacy. This research applied an experimental method with 2 x 2 factorial analysis level. Data analysis in this research used analysis of two-way variance (ANOVA) and t-test. The results of this research are (1) there is differences in learning achievement of science learning between the group applied SDL and the group applied conventional learning model; (2) there is an interaction between the learning model and student self-efficacy on student learning achievement; (3) learning achievement of high efficacy students with SDL learning model has insignificant differences with conventional learning models; (4) learning achievement of low efficacy students with conventional learning models is higher than SDL learning model.